2019
DOI: 10.1039/c9nj01733j
|View full text |Cite
|
Sign up to set email alerts
|

Plant-mediated synthesis of AgPd/γ-Al2O3 catalysts for selective hydrogenation of 1,3-butadiene at low temperature

Abstract: Plant-mediated synthesis of bimetallic AgPd/γ-Al2O3 catalysts for selective hydrogenation of low-temperature 1,3-butadiene was reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 34 publications
3
23
0
Order By: Relevance
“…This low-intensity peak turns into a small broadband within the 2θ range from 38.7 to 41.6 • for the bimetallic 3% AgPd-Fe 3 O 4 sample. This band, along with the glimpsed wide bump centered at 45.5 • , is in full agreement with previously reported XRD patterns of bimetallic AgPd alloys presenting fcc crystalline structure [41][42][43][44], especially with those containing Ag:Pd molar ratio of 2:8 [42] or between 3:7 and 1:9 [41]. The main XRD diffraction of metal Pd is barely observed for the 2% Pd-Fe 3 O 4 sample and the region becomes totally flat for the 1% Pd-Fe 3 O 4 , which is coherent to the quantitative detection limit (<2%) associated to the XRD technique for multiphase mixtures [45].…”
Section: Development Of Nanocomposite (Ag)pd-fe 3 O 4 Materialssupporting
confidence: 92%
See 3 more Smart Citations
“…This low-intensity peak turns into a small broadband within the 2θ range from 38.7 to 41.6 • for the bimetallic 3% AgPd-Fe 3 O 4 sample. This band, along with the glimpsed wide bump centered at 45.5 • , is in full agreement with previously reported XRD patterns of bimetallic AgPd alloys presenting fcc crystalline structure [41][42][43][44], especially with those containing Ag:Pd molar ratio of 2:8 [42] or between 3:7 and 1:9 [41]. The main XRD diffraction of metal Pd is barely observed for the 2% Pd-Fe 3 O 4 sample and the region becomes totally flat for the 1% Pd-Fe 3 O 4 , which is coherent to the quantitative detection limit (<2%) associated to the XRD technique for multiphase mixtures [45].…”
Section: Development Of Nanocomposite (Ag)pd-fe 3 O 4 Materialssupporting
confidence: 92%
“…This lowintensity peak turns into a small broadband within the 2θ range from 38.7 to 41.6° for the bimetallic 3% AgPd-Fe3O4 sample. This band, along with the glimpsed wide bump centered at 45.5°, is in full agreement with previously reported XRD patterns of bimetallic AgPd alloys presenting fcc crystalline structure [41][42][43][44], especially with those containing Ag:Pd molar ratio of 2:8 [42] or between 3:7 and Furthermore, semiquantitative analysis of the XRD data by X'Pert Highscore Plus software confirmed the major presence of an orthorhombic Fe 3 O 4 structure in all (Ag)Pd-Fe 3 O 4 catalysts from Figure 3. Only for 1% Pd-Fe 3 O 4 and 3% AgPd-Fe 3 O 4 samples did the semiquantitative phase analysis provide a minor coexistence with the cubic Fe 3 O 4 structure (ca.…”
Section: Development Of Nanocomposite (Ag)pd-fe 3 O 4 Materialssupporting
confidence: 92%
See 2 more Smart Citations
“…16,17 Recently, bimetallic nanoparticle catalysts have attracted much attention in heterogeneous catalysis. 13,[18][19][20][21][22] Bimetallic catalysts generally show better catalytic performance than the corresponding monometallic catalysts because catalytic activity could be enhanced by synergistic effects between different components. 23 Hou et al reported that the bimetallic PdNi/g-Al 2 O 3 catalyst shows higher BD hydrogenation activity and 1butene selectivity than Pd/g-Al 2 O 3 and Ni/g-Al 2 O 3 catalysts.…”
Section: Introductionmentioning
confidence: 99%